2010
DOI: 10.1080/10242694.2010.501185
|View full text |Cite
|
Sign up to set email alerts
|

Military Expenditure and Granger Causality: A Critical Review

Abstract: A large literature has used tests for Granger (1969) non-causality, GNC, to examine the interaction of military spending with the economy. Such tests answer a specific although quite limited question: can one reject the null hypothesis that one variable does not help predict another? If one can reject, there is said to be Granger causality, GC. Although the limitations of GNC tests are well known, they are often not emphasised in the applied literature and so may be forgotten. This paper considers the economet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…See for instance Joerding (1986), Chowdhury (1991) Dakurah et al (2001, Abu-Bader and Abu-Qarn (2003), Dunne and Nikolaidou (2005), among others. For detailed discussion see Dunne and Smith (2010). 5 Some also apply the augmented Solow growth model, such as Knight et al (1996), andYakovlev (2007).…”
Section: The Three Approachesmentioning
confidence: 99%
“…See for instance Joerding (1986), Chowdhury (1991) Dakurah et al (2001, Abu-Bader and Abu-Qarn (2003), Dunne and Nikolaidou (2005), among others. For detailed discussion see Dunne and Smith (2010). 5 Some also apply the augmented Solow growth model, such as Knight et al (1996), andYakovlev (2007).…”
Section: The Three Approachesmentioning
confidence: 99%
“…It uses Granger non-causality tests for this purpose for two reasons. First, because they allow the complexity of the underlying theoretical arguments to be avoided, by simply considering bivariate relations between military spending and economic growth (Dunne and Smith, 2010). Secondly, because they allow the use of recently developed tools to investigate structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…shown to impact on economic growth and development, as well as other economic variables such as international debt or corruption (see for example, Dunne et al, 2005;Collier and Hoeffler, 2006;Aizenman and Glick, 2006;Lin and Ali, 2009;Pieroni, 2009;Smyth and Narayan, 2009;Heo, 2010;Dunne and Smith, 2010;Alptekin and Levine, 2011;Kollias and Paleologou, 2013). Moreover, research has found that there may exist a trade-off between spending on the military and other areas such as health and education, the so-called guns-vs.-butter trade-off (see for example, Russet 1969;Deger 1985;Palmer 1990).…”
Section: Studying Military Expenditures Is Important For Many Reasonsmentioning
confidence: 99%